Budaya Spiritual dan Keunggulan Personality - Lukmanul Hakim; Sarilah Sarilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT The purpose of this research is to describe spiritual culture and its forming factors, as well as the steps of functionalization of spiritual culture, and their impact on personality excellence. Methods The research uses a qualitative approach with a case study design. The research sample used purposive sampling and snowball sampling. The results of the study describe the spiritual culture that forms the superiority of the student's personality in the form of: spirit values, piety (devotion), healthy competition (competitive), integration (values, knowledge, and attitudes), social sensitivity, and stability in action (decision making). . This is influenced by leadership factors, general referrals, and a value system that is formed through the process of internalization and socialization of spiritual culture. The conclusion of the study, that spiritual culture that forms the superiority of student personality can be seen in the following spiritual dimensions: transcendence or belief, meaning and purpose of life, life mission, sanctity of life, spiritual satisfaction, altruism, idealism, awareness of the suffering of others, and spirituality of a person will color his life. Keywords: Excellent Personality, Spiritual Culture.